Simulation of pulse oximeter data in simulink environment - Thet Mon Aye. (2009)
This report will focus on the analysis of pulse oximeter data in the VHDL software in a way of processing a Simulink block diagram model in order to produce a VHDL representation of the model. The VHDL model consists of the behavioral and structural definitions mapped from the Simulink model in order to develop and simulate a digital control algorithms using the Matlab and convert to the VHDL code. This would then be synthesized into digital logic hardware for implementation on devices such as FPGAs (Field Programmable Gate Arrays).